Augmented reality hologram - Ng, Jing Heng (Nanyang Technological University, 2020)
This paper presents the development of a mobile application that enables the creation of holographic objects and display of holographic objects on mobile devices. This project builds on the existing Augmented Reality Hologram application, with a focus on enhancing user experience through redesigning the user interface and implementation of new functionalities to appeal to the mass market. Improvements made on top of the original application fill crucial research gaps in existing AR applications such as rendering multiple objects in the scene, user-created AR objects and integration with online libraries. Specifically, the new functionalities implemented include an improved algorithm to accurately anchor holographic objects, ability for users to place multiple, distinct AR objects in the virtual scene simultaneously and integration with 3rd party APIs (Pixabay and YouTube) to offer users a wider variety of holographic objects to place in the scene and interact with. Through the enhancements made to the user interface, the newly designed application ultimately aims to reduce the barriers to entry of creating AR objects such that the AR technology is within the reach of the wider public. ARHolo had been published on the Google Play Store and is accessible to Android device users.